Assessing the Demographic and Economic Parameters that Determined the Residential History of Medieval Central Greece: the Case of Western Sterea Hellas - Terezakis, George (Studia Ceranea, 2025)
The principal objective of this study is to investigate the demographic and economic parameters that shaped the settlement dynamics of medieval Central Greece (Sterea Hellas) over a broad chronological span extending from the 12th to the 16th century. Given the fragmentary and often insufficient nature of surviving Byzantine-era sources, the most effective means of avoiding vague generalizations is to adopt a long-term analytical perspective, using the comparatively rich Ottoman data from the mid-15th to the 16th century as a basis for retrospective interpretation. Throughout this period, the spatial organization of the region – particularly the contrast between the mountainous and semi-mountainous zones of Aetoloakarnania and Evrytania and the lowland plains of Fthiotida – profoundly influenced patterns of agricultural production and pastoral activity. Documentation from the late Byzantine period regarding settlement structures remains limited, with narrative sources, primarily historiographical in nature, offering only sporadic and anecdotal references. By contrast, the Ottoman fiscal censuses (tahrir defters) provide a far more systematic dataset, recording local tax revenues and offering detailed information on the composition of the taxable population, thus enabling a more grounded reconstruction of settlement and economic patterns in the region. The available evidence points to a relatively smooth transition following the establishment of Ottoman rule in the region. In this context, the consolidation of political authority contributed to the stabilization and even revitalization of the local urban network and the broader settlement landscape, suggesting that the process of Ottoman integration fostered a degree of continuity and structural reinforcement rather than abrupt disruption.